An FTIR method for the analysis of crude and heavy fuel oil asphaltenes to assist in oil fingerprinting. (September 2016) - Riley, Brenden J.; Lennard, Chris; Fuller, Stephen; Spikmans, Val
Highlights: ATR-FTIR analysis of C5 asphaltenes from ten different crude and heavy fuel oils. Visual and peak height ratio comparisons of asphaltene FTIR spectra. 100% discrimination of all ten oil samples was achieved using this method. This method correctly identified the source of a weathered oil sample. FTIR demonstrates significant potential for application in oil fingerprinting. Abstract: A proof-of-concept spectroscopic method for crude and heavy fuel oil asphaltenes was developed to complement existing methods for source determination of oil spills. Current methods rely on the analysis of the volatile fraction of oils by Gas Chromatography (GC), whilst the non-volatile fraction, including asphaltenes, is discarded. By discarding the non-volatile fraction, important oil fingerprinting information is potentially lost. Ten oil samples representing various geographical regions were used in this study. The asphaltene fraction was precipitated from the oils using excess n -pentane, and analysed by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR). Based on visual interpretation of FTIR spectra along with peak height ratio comparisons, all ten oil samples could be differentiated from one another. Furthermore, ATR-FTIR was not able to differentiate a weathered crude oil sample from its source sample, demonstrating significant potential for the application of asphaltenes in oil fingerprinting.